ANALISIS PENDIDIKAN KARAKTER DALAM MEMPERSIAPKAN PUBERTAS MENUJU GENERASI EMAS INDONESIA 2045 (Jurnal Pendidikan Dasar, 2019)
Indonesian government launched Gold Generation 2045 to anticipate demographic bonus that projected to be at the peak in 2030. Character education in preparing students for puberty were critical and potential intervention to build the principles of healty and responsible individual nowaday and in the future. This article aims to review the situastion and conduct SWOT analysis by disscuss as much as 13 articles and some research findings or surveys as well as books. Character education in Kurikulum 2013 have beed developed and still being enhanced to make it affordable and relevant to ideal education principles for Indonesian students. The role of school, family, and community are noteworhy to achieve holistic and integrated education goals.